THE EFFECTIVENESS OF REGIONAL REGULATION ENFORCEMENT RELATED TO THE MANAGEMENT OF COVID-19 IN STREET SELLERS IN JAKARTA BARAT - Bayquni Bayquni (Moestopo International Review on Social, Humanities, and Sciences, 2021)
Enforcement of local regulations regarding the handling of Covid 19 against street vendors in the West Jakarta Administrative City is still ineffective based on the lack of discipline on street vendors to comply with Health Protocols and the efforts of Satpol PP in enforcing PERDA to overcome Covid 19. While the theory used is effectiveness according to Tyson & Jackson, which consists of 1) Briefing, (2) Delegation, (3) Control, (4) Accountability, (5) Efficiency, (6) Coordination, (7) Adaptation, (8) Social Systems and Individual Expectations. The research method in this research uses qualitative methods. A qualitative approach is used because it involves the formulation of symptoms, information, or information regarding the enforcement of local regulations on Covid-19 prevention by Satpol PP against street vendors in West Jakarta Administrative City. The use of qualitative methods is supported by a project map on the Nvivo 12 application. The research findings show that the implementation of the enforcement of the Covid-19 countermeasures PERDA on street vendors in West Jakarta City Administration by Sat Pol PP, namely: (1) Satpol PP in enforcing the Covid 19 countermeasures PERDA in street vendors is still not fully effective in the implementation of delegation and control , accountability, efficiency, coordination and adaptation; and (2) The concept of improvement that can be carried out is the enforcement of the regulation on Covid 19 prevention by implementing humanist normative pattern of street vendor control, namely performance management of street vendors with environmental control, social services and economic empowerment of street vendors as business actors in the economic system. community organized according to the conditions of the Covid pandemic 19.